Functional status in a geriatric oncology setting: A review. Issue 6 (November 2019) - Couderc, Anne-Laure; Boulahssass, Rabia; Nouguerède, Emilie; Gobin, Nirvina; Guérin, Olivier; Villani, Patrick; Barlesi, Fabrice; Paillaud, Elena
Abstract: Background: Comprehensive Geriatric Assessment (CGA), is used in older patients with cancer to identify frailties, which can interfere with specialized treatment, and to help with therapeutic care. Functional Status (FS) is a domain of CGA in which Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) are evaluation tools. Objective: Our study reviewed the data available on the most frequently used tools to assess ADL and IADL in a geriatric oncology setting and their predictive values on overall survival (OS), toxicity, treatment feasibility or decision and postoperative complications. Design: This review was based on a systematic search of the MEDLINE® database for articles published in English and French between January 1, 2010, and December 31, 2017. In the final analysis, 40 out of 4061 studies were included. Results: The most common ADL and IADL scales used are the Katz ADL (KL-ADL) in 25 studies and the Lawton IADL (IADL8 ) in 22 studies. FS is predictive of OS in 11 out of 24 studies, chemotoxicity in 2 out of 7 studies, treatment feasibility in 2 out of 5 studies, treatment decisions in 2 out of 3 studies, and postoperative complications in 4 out of 6 studies. Conclusion: FS is of prognostic value in a geriatric oncology setting despite heterogeneous methodology and inclusion criteria, in the studies included. Additional research is needed to explore more precisely the prognostic value of FS in overall survival, toxicity, treatment feasibility or decision and postoperative complications, in older cancer patients.